Analisis Problem Solving Berdasarkan Kemampuan Awal Peserta Didik - Riski Fitri Damayanti; Arif Hidayat; Supriyono Koes Handayanto (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This study aims to explore students’ problem solving. This study is a quantitative with descriptive analysis. The research sample consisted of 92 students from Surabaya's Ta'miriyah High School. The research instrument consisted of six item description items that had passed the expert validation process with a reliability coefficient of 0.805.The results of descriptive analysis show that the problem solving ability of students with high initial ability is higher than the problem solving ability of students with low initial ability and the highest problem solving aspects of initial high and low ability students is useful description and the lowest problem solving aspect is a logical progression.Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan problem solving peserta didik. Penelitian ini adalah penelitian kuantitatif dengan analisis deskriptif. Sampel penelitian terdiri dari 92 peserta didik yang berasal dari SMA Ta’miriyah Surabaya. Instrumen penelitian berupa soal uraian sebanyak enam butir yang telah melewati proses validasi ahli dengan koefisien reabilitas sebesar 0,805. Hasil analisis deskriptif menunjukkan bahwa kemampuan problem solving peserta didik berkemampuan awal tinggi lebih tinggi daripada kemampuan pemecahan masalah peserta didik berkemampuan awal rendah dan aspek paling tinggi kemampuan problem solving peserta didik berkemampuan tinggi dan rendah adalah useful description dan aspek terendah kemampuan problem solving adalah logical progression.